PENGARUH MODERASI PENDAPATAN ASLI DAERAH TERHADAP HUBUNGAN BELANJA MODAL DAN KEMANDIRIAN KEUANGAN DAERAH - SUGIONO, SUHANDARINI (Jurnal Akuntansi AKUNESA, 2014)
Financial independence of the region shows the government's ability to finance its own activities of governance, development and services to the people who have paid taxes and levies as a source of local revenue needed without relying on central government funding. The purpose of this study is to determine the effect of moderating the relationship capital expenditure and financial independence of the region.This study uses secondary data began the period 2009 to 2013 were obtained from the Regional Asset Finance Agency and the East Java province. Research sample as amount of 180 from 28 districts and 8 cities. The analytical method used is a simple regression and Moderated Regression Analysis. The results of the analysis indicate that capital expenditures affect Financial Independence Regional and Local Revenue is able to moderate the relationship between Capital Expenditure and Financial Independence Regional.   Keywords: Capital Expenditure, Financial Independence of Regional and Local Revenue